The Influence of Solvent Variety and Drying Method on Physical, Chemical and Functional Characteristic of Shark Skin Gelatin - Made Astawan; Tita Aviana (Jurnal Teknologi dan Industri Pangan, 2003)
Gelatin is a denaturation product of collagen and has been widely utilized for foods, photography uses, medical materials, and culture materials for microorganisms. Recently, gelatin’s uses has expanded to new applications such as health foods. Gelatin of land animal origin such as bovine and porcine has been mainly used. However, gelatin with new properties is desired to develop expanded applications. In this research gelatin was made from shark skin. The shark skin collagen was distended by acetic acid solution (acid process) and sodium hydroxide solution (alkali process), and gelatin was then extracted at 80oC of water. The extracted gelatin was dried by vacuum drying and freeze drying to obtain powder product. Shark gelatin produced by the combination of alkali and vacuum drying process (OVB gelatin) had better qualities on yield, water content, gel strength, melting point, and emulsion stability as compared to the others. Sensory evaluation indicated that shark gelatin had lower values in color, odor, and performance as compared to the commercial gelatin of fish, pig and bovine (SKW Biosystem). However, as compared to the commercial gelatins, OVB gelatin had a similar values on gel strength (202 bloom) and emulsion stability (100%), but higher values on viscosity (8 cP) and pH (9.3). Those values indicated that ray skin gelatin can be used to substitute the commercial gelatin in some food industries Key words: Gelatin, shark, melting point, and emulsion stability